English Student book 4 - "Wren,Wendy" (Nelson: Walton-on-Thames, 1996)
Nelson English International teaches the skills and craft of quality writing, catering for the 6-12 year age range, and provides a six year programme of study. It is easily managed in the classroom, with three components at each level: a Student Textbook; a Student Workbook; and a Teacher Resource Book.
Keywords: English language -Composition and exercises